PENGARUH MODEL PEMBELAJARAN KOLABORATIF TIPE BUZZ GROUP TERHADAP KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN TEMATIK KELAS V MADRASAH IBTIDAIYAH - Selvia, Rida; Rahmad, Rahmad; Mahmudah, Istiyati (Universitas Islam Lamongan, 2024)
This research aims to determine the effectiveness of the Buzz Group-type collaborative learning model on students' active learning. The method used in this research is quantitative, the research design used in this research is quasi-experimental (Quasi Experiment) consisting of two categories, namely the control and experimental categories. The subjects of this research are class V students at MIS Darul Ulum which consists of two classes, namely class VA (Control) and VB (Experiment). The research instruments were observation sheets and questionnaires to measure students' learning activity. The results of the research show that the Buzz Group-type collaborative learning model is effective in actively learning Indonesian for class V students with a significance value of 0.000. This research contributes by providing empirical evidence that the Buzz Group-type collaborative learning model can increase student learning activity, offering an effective alternative to teaching methods in elementary schools.